The effect of e-WOM on tourists’ experience at Malaysian island beach resorts - Putit, Lennora; Mohammed Shobri, Nor Diyana; Ahmad Suki, Amirah (European Publisher, 2024)
In recent years, customer experience has strengthened its presence within the global tourism industry generally viewed as an experience-intensive sector. Despite that, major influences of customer experience are still debatable amongst academics and business practitioners alike. This study aimed to examine the extent to which electronic word of-mouth (or eWOM) forms of communication influenced total guest experience, involving both escapism and aesthetic experience elements. Using a quantitative research design, 433 usable survey feedbacks were collected from target respondents comprising tourists staying at major island beach resorts in Malaysia. Data analyses were carried out using a structural equation modelling approach in testing the hypothesized assumptions. Findings revealed a significant relationship between eWOM and escapism experience. On the contrary, no significant relationship was observed between eWOM and aesthetic experience. This study makes a contribution to the academic literature in which it establishes the importance of eWOM on tourists’’ experience. Several practical implications also were further discussed.